2001
DOI: 10.1007/s001150170006
|View full text |Cite
|
Sign up to set email alerts
|

Kontralaterale und ipsilaterale repetitive transkranielle Magnetstimulation bei Parkinson-Patienten

Abstract: In seven women and two men with Parkinson's disease, Hoehn and Yahr stage 1 or 2, the effect of repetitive transcranial magnetic stimulation (rTMS) was evaluated. Primary endpoint outcome measure was the changing of the motor items of the Unified Parkinson's Disease Rating Scale (subscale III of UP-DRS) 24 h after stimulation. Kinesiologic tests and writing samples were secondary outcome measures. After discontinuing all medication, stimulation was performed with 5 Hz at 90% of the motor threshold over the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…The behavior of the current density distribution directly under the coil center was very similar to the analogous atrophy models, but far less predictable along the widened sulci borders, similar to the results seen in stroke (Wagner 2001;Wagner et al 2005) and heterogeneity studies (Wagner 2001;Miranda et al 2003). There were locations directly below the most posterior portion of the figure-of-eight coil, along the widened central sulci border, where current density magnitudes were within ±15% of the maximums found under the coil center (3.59, −0.85, 6.61, and 14.35%, respectively for the base, 95, 90, and 85% widened sulci models).…”
Section: Effects Of Widened Sulci On the Induced Stimulating Currentssupporting
confidence: 65%
See 3 more Smart Citations
“…The behavior of the current density distribution directly under the coil center was very similar to the analogous atrophy models, but far less predictable along the widened sulci borders, similar to the results seen in stroke (Wagner 2001;Wagner et al 2005) and heterogeneity studies (Wagner 2001;Miranda et al 2003). There were locations directly below the most posterior portion of the figure-of-eight coil, along the widened central sulci border, where current density magnitudes were within ±15% of the maximums found under the coil center (3.59, −0.85, 6.61, and 14.35%, respectively for the base, 95, 90, and 85% widened sulci models).…”
Section: Effects Of Widened Sulci On the Induced Stimulating Currentssupporting
confidence: 65%
“…These will obviously depend on the geometry and electrical tissue distributions in the regions of the sulci, but earlier studies have clearly shown the effects of heterogeneities, as those operating at sulcal borders, can be extremely significant (Wagner 2001: Wagner et al 2004, 2005Miranda et al 2003). As is supported by studies examining corner points in other electromagnetic models (Deeley 1990), we hypothesize that the effects will be most extensive at regions where the border geometries result in corner regions, such as could be seen along irregular edges of scar tissue along an infarction border.…”
Section: Widened Sulci Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies [32][33][34]39,45,52,54,55,63] tested the effects of only one rTMS session, while the remaining administered a higher number of sessions, ranging from 2 to 20. Most studies, especially those targeting M1, SMA and DLPFC, administered high-frequency stimulation (24 of 40 studies) [29][30][31][32][33][34][37][38][40][41][42][43][44][49][50][51][53][54][55][57][58][60][61][62], while lowfrequency stimulation was employed primarily in studies targeting other regions. The intensity of stimulation ranged from 20% of motor threshold to 120%.…”
Section: Rtms Studies In Pdmentioning
confidence: 99%